The impact of equity capital on the bank's profitability: Evidence from Vietnam's banking system - Ngo Thanh Xuan; Phương Linh Bui; Minh Huong Le (Journal of Banking and Financial Economics (JBFE), 2021)
From 2008 to 2019, this research examines the effect of equity capital on the profitability of 24 Vietnamese commercial banks. The research findings indicate that, when ROAA and ROAE are used to measure the bank's profit, the equity capital ratio (CAP) has a statistically significant positive effect on the ROAA while having a negative effect on the ROAE. Between 2013 and 2019, the CAP variable has a positive effect on the ROAA and ROAE, indicating that banks with a larger equity capital ratio achieved higher profitability. Furthermore, the deposits-to-assets ratio (DTA) and loan-loss reserves ratio (LLR) both have a negative effect on both proxies for bank profitability, although bank size (SIZE) has a negligible effect on bank profits in the majority of circumstances. Additionally, the rate of GDP growth and inflation (INF) have a beneficial effect on the bank's profitability. The study's objective is to present some critical policy implications for bank executives about the importance of adequate equity capital for the bank's sustainability development.
Keywords: G20; G21; 330; bank equity capital; bank profitability; commercial banks